Pengaruh Pemberian Aromaterapi Lemon terhadap Penurunan Dismenore pada Remaja Putri - Antri Ariani; Yanyan Mulyani; Rosifa Rosifa (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
Dysmenorrhea is also known as menstrual cramps or menstrual pain. In Indonesia, there is a prevalence of dysmenorrhea of 64,5% in adolescents aged 17-24 years. Which affect fatigue, pain in the area below the waist, feelings of anxienty and tension, headaches, confusion, nausea and vomiting, diarrhea, stomach cramps and abdominal pain and activity disturbances. The most common symptons felt by midwifery students who experienced dysmenorrhea were low back pain and lower abdominal pain. In English, dysmenorrhea is often referred to as a